(3GdZQQ hGdOQQs - (3YHjO Gddg Hf eMeO GdgGTej GdMSjfj GdaQZGfj HQgGf GdOjf, GdeYQha HGdYHQj , hjfYJ HGdTQja GdeQJVj,J (B743 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf JChjd GjI bGd Gddg JHGQc hJYGdi (B( (3hjSGdhfc Yf GdQhM bd GdQhM ef CeQ QHi heG ChJjJe ef GdYde EdG bdjdkG (B) s
(3BNQgG (B:s
(3BNQ GdehLhO eLdS BNQ hJChjd CjI Ef SCd SGFd Yf bhdg JYGdi (B( (3hdG Jbhdf dTF Efi aGYd Pdc ZOkG ZdG Gf jTGA Gddg (B) (3GdeYfi Ef Gddg JYGdi Hjfgi Yf Cf jbhd GdYHO Efi aGYd Pdc ZOkG s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B197 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B136s
Keywords: (3GdCOHs